Condition monitoring of faculty air conditioning system - Akmalhabibi, Rosli (2013)
This thesis writing deals with the study of Condition based maintenance, CBM, defined as preventive task is performed at certain condition of the equipment. This strategy is much more cost effective than maintenance on failure. When running to failure, an unplanned interruption to production or service is induced. Also a collateral damage may lead to costly consequences. Pump mostly has cause energy loss low performing during task time. The cause of the pump error is because of the vibration in the pump itself. Lack of the information and the knowledge of the vibration error can cause damage on the pump. The prediction technique can ensure the safety of the pump. One way to check the errors occur on the pump is using DASYLAB software. DASYLAB software will calibrate with the tri-axis accelerometer sensor to grab the data and convert it into a measureable data. Some condition indicators are monitored to observe deterioration and detect onset of failures. With exception of vibration analysis, there is a deficiency of experimental studies that investigate diagnosis of rotor related faults. To see the errors on the pump, the vibration data will be converting into the FFT graph and the pattern of the error can be seeing based on the ISO 10816-3. The result should show the problem occur base on the FFT vibration graph. In the future plan, the, the technique can be implement around the Faculty of Mechanical